2015
DOI: 10.1016/j.enpol.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Public policy influence on renewable energy investments—A panel data study across OECD countries

Abstract: Panel data study on the effectiveness of policies to induce RE investments. Novel combination of datasets (BNEF/IEA) in solar, wind and biomass sectors. FIT proves to be more effective than subsidies for less mature technologies. RPS and tradable permit systems seem more effective for mature technologies. A long-term strategic planning framework is useful to attract institutional investors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 344 publications
(159 citation statements)
references
References 57 publications
5
127
0
Order By: Relevance
“…Some of the most common public policy measures to encourage renewables include subsidies, quota policies, direct investment, research and development, feed-in tariffs, and green certificates. Polzin et al (2015) highlighted the importance of establishing reliable frameworks and long-term policy objectives on the growth of RE but revealed that these have to be technology-specific. Those frameworks could be influenced by both domestic and international factors such as characteristics of domestic political institutions or by what other countries, or group of countries (e.g.…”
Section: Political Factorsmentioning
confidence: 99%
“…Some of the most common public policy measures to encourage renewables include subsidies, quota policies, direct investment, research and development, feed-in tariffs, and green certificates. Polzin et al (2015) highlighted the importance of establishing reliable frameworks and long-term policy objectives on the growth of RE but revealed that these have to be technology-specific. Those frameworks could be influenced by both domestic and international factors such as characteristics of domestic political institutions or by what other countries, or group of countries (e.g.…”
Section: Political Factorsmentioning
confidence: 99%
“…However rigorous policy evaluations of specific programs are still rare. Studies have mainly focused on broad energy policies on nation-wide basis, including among others feed-in tariffs (FiT) [7][8][9][10][11], renewable portfolio standards (RPS) [12][13][14][15][16], tenders and tax incentives [17]. This growing body of empirical evidence have concentrated mostly on FiT and RPS policies as they have vastly used [18].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Yin and Powers [16] suggests a positive relationship between RPS and the share of electricity capacity based on RE but only conditional on level of policy stringency. Polzin et al [7] also suggest that RPS can accelerate the diffusion process of RE technologies by reducing technological and regulatory risk associated with investments in RE projects. Aspects of RPS policy are further analysed by Shrimal and Kniefel [12] who demonstrate that those with a sale requirement are more effective than those with a capacity requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Market-based incentives such as GHG emissions trading systems represent the theoretical optimum as argued by climate and energy economics since the early 1990s [55,56]. However, due to the lack of global mechanisms, second-best instruments are required.…”
Section: Innovation Policymentioning
confidence: 99%